The local indigenous food of Sarawak as potential functional food - Hui-Yan, Tan; Sarbini, Shahrul Razid (Wiley-Blackwell Publishing, 2024)
The local people of Sarawak commonly made unique dishes out of the local distinctive resources for its health beneficial nutrients. Yet, many potentials of the local Sarawak food ingredients are less likely to be exploited. One of the main produces of Sarawak is the starch from Metroxylon sagu. Our study reviewed that sago starch is not only active in health beneficial bioactivities such as antioxidative, it also possesses positive prebiotic response. Other local indigenous fruits, vegetable and spices of Sarawak as potential functional food includes Sarawak pepper; midin, the edible fern; terung asam, the sour eggplant; dabai, the Bornean olive; engkalak, the Bornean avocado; Terap, the local ‘jackfruit’; embangan, the local wild mango; and the edible palm heart (EPH) from palm tree. Research on the edible fern (midin), edible palm hearts (umbut), spices such as turmeric and pepper from Sarawak has revealed a positive functionality in terms of prebiotic potential, antioxidative, antimicrobial and many more. Conclusively, the wide food varieties of Sarawak are potential functional food. Therefore, this work aimed to publicise the health beneficial functionalities of the local indigenous food which then value-added the rare local food resources, and boost the local farmer's production and economic status.